The Learning Implementation of Project Based Learning (PjBL) to Analyze Students’ 4C Skills Ability - Septi Umalia Firda; Titin Sunarti (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2022)
This research aims to analyze the increase critical thinking and creative thinking skills furthermore to describe collaborative skills and communication skills with PjBL method. This research quantitative type. Pretest-Postest given for critical thinking skills and creative thinking skills, while observation sheet for communication skills and collaboration skills. The populations students of grade X MNS, research samples 34 students of grade X MNS 2 even semester academic year of 2021/2022, with convenience sampling technique. Research instruments are assessment sheets of critical thinking, creative thinking, communication, and collaboration skills. To determine the increase critical thinking and creative thinking skills are analyzed by One sample T test and N-gain, while for communication skills and collaboration skills are analyzed by quantitative descriptive. T-test results showed a significant difference between pre test and post test results. N-gain analysis results showed that an increase creative thinking skills of 0,72 “moderate” category, critical thinking skills of 0,77 “high” category. While the average score of students’ collaboration skills and communication skills are 64,85 and 65,07 respectively with good category. Conclusion of this research is given, students experienced an increase in creative thinking and critical thinking skills, furthermore for the communication and collaboration skills are categorized as good.